Cost-effective energy and carbon emissions optimization in building renovation (annex 56): executive summary for policy makers - Almeida, Manuela Guedes de (2017)
This guidebook was compiled to raise awareness among the players that can influence policies and standard definition and to engage them in the subjects of energy efficiency and renewable energy sources in the context of building renovation. Existing buildings present a tremendous potential, not only to reduce energy use and emissions, but also on other areas of the political agenda. It is the objective of this guidebook to highlight how energy related building renovation is a policy tool to achieve broad benefits to society